2018
DOI: 10.1016/j.biocontrol.2017.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Granulobasidium vellereum (Ellis &Cragin) Jülich, a promising biological control agent

Abstract: Studies involving biological control of wood decay fungi and pests in forest areas are scarce. The basidiomycete Granulobasidium vellereum (Ellis & Cragin) Jülich has been isolated as wood endophyte from London Plane trees (Platanus acerifolia (Ait.) Willd). This basidiomycete produces a variety of sesquiterpenes with antifungal activity. In this study we evaluated the potential activity of G. vellereum against wood decay fungi and fungi associated with the ambrosia beetle Megaplatypus mutatus Chapuis, an impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…This finding is supported by the research of Gholami et al, [43] who reported four basidiomycete isolates as having potential antifungal activity against the take‐all fungus, Gaeumannomyces graminis , in vitro using dual culture technique. Additionally, the fungal basidiomycete Granulobasidium vellereum , a wood endophytic fungus, possesses antifungal activity against wood decay fungi owing to its variety of sesquiterpenes [44]. Moreover, the antioxidant properties of the endophytic fungus P. caribaeo quercicola align with those found in Phellinus merrillii reported by Chang et al [45] Another basidiomycete fungal endophyte, Schizophyllum commune is reported to have good antioxidant potential [46].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is supported by the research of Gholami et al, [43] who reported four basidiomycete isolates as having potential antifungal activity against the take‐all fungus, Gaeumannomyces graminis , in vitro using dual culture technique. Additionally, the fungal basidiomycete Granulobasidium vellereum , a wood endophytic fungus, possesses antifungal activity against wood decay fungi owing to its variety of sesquiterpenes [44]. Moreover, the antioxidant properties of the endophytic fungus P. caribaeo quercicola align with those found in Phellinus merrillii reported by Chang et al [45] Another basidiomycete fungal endophyte, Schizophyllum commune is reported to have good antioxidant potential [46].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to fungal crude extracts, fungal volatile organic compounds (VOCs) have also been investigated for their antagonistic effect against ambrosia fungi. Robles et al (2018) demonstrated that Granulobasidium vellereum, a wood endophyte of Platanus acerifolia (Aiton) Willd (Platanaceae), could successfully inhibit mycelial growth of Raffaelea sp. associated with Megaplatypus mutatus in vitro, through the emission of fungal VOCs.…”
Section: Fungi With Antifungal Activity Against Ambrosia Fungimentioning
confidence: 99%